1978
DOI: 10.1021/ic50188a027
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of nitrosylpentaammineruthenium(II) with aromatic aldehydes in aqueous base. An example of catalyzed metal ion hydrolysis

Abstract: Evidence is presented that the reaction of [RU(NH,)~NO]~+ with several aromatic aldehydes in 0.1 M NaOH forms tran~-Ru(NH~)~(0H)N0~+ as the exclusive product, with the aldehyde serving as a catalyst. Electronic spectral data suggest that the reaction takes place via nucleophilic attack of the amido ligand trans to the nitrosyl group at the carbonyl of the aldehyde to form an unstable imine intermediate which hydrolyzes at the metal-nitrogen bond to yield the hydroxo product and quantitatively regenerate the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[70][71][72] The presence of trace metal ions may lead to various drug degradation pathways. One example is metformin degradation catalyzed by a metal ion (M n + ) to form a drug degradation product as shown in Figure 9.…”
Section: Metal Ion-catalyzed Reactionmentioning
confidence: 99%
“…[70][71][72] The presence of trace metal ions may lead to various drug degradation pathways. One example is metformin degradation catalyzed by a metal ion (M n + ) to form a drug degradation product as shown in Figure 9.…”
Section: Metal Ion-catalyzed Reactionmentioning
confidence: 99%
“…Previous studies have demonstrated that aldehydes and ketones with no a hydrogens undergo an entirely different (and much slower) reaction involving the ammonia ligand trans to the nitrosyl group. 18 The most apparent synthetic potential of reactions 1 and 2 is for oxidative ring opening and bifunctionalization of cyclic ketones under very mild conditions, thus representing an excellent alternative to present oxidative cleavage methods such as Marshall's19 cleavage of -diketone monothioketals or the known oxidative cleavage of cyclic olefins20 for the synthesis of macrocyclic compounds or compounds containing linear chains with fixed stereochemistry.…”
mentioning
confidence: 99%